2022
DOI: 10.1016/j.apmr.2022.01.142
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Functional Outcomes in Cancer Rehabilitation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 359 publications
(381 reference statements)
2
33
0
Order By: Relevance
“…In this scenario, rehabilitation plays a key role in the management of BC survivors with growing evidence highlighting its positive effects in improving functional outcomes and psychosocial well-being of BC patients ( Reid-Arndt et al, 2009 ; Zaidi et al, 2017 ; Kudre et al, 2020 ; Sleight et al, 2022 ). Hence, rehabilitation might improve the symptoms of patients with breast cancer–related lymphedema ( Invernizzi et al, 2019 ; Michelotti et al, 2019 ; de Sire et al, 2021a ; Carretti et al, 2022 ; Muñoz-Alcaraz et al, 2022 ; Omar et al, 2022 ), cancer-related fatigue ( Wirtz and Baumann, 2018 ; Adams et al, 2019 ; Invernizzi et al, 2020b ; Marechal et al, 2020 ; Licht et al, 2021 ), axillary web syndrome ( de Sire et al, 2020 ; Ravichandran et al, 2020 ; Tay et al, 2021 ), aromatase inhibitor–induced arthralgia ( Harris et al, 2012 ; Winters-Stone et al, 2012 ; Grizzi et al, 2020 ), and cancer treatment–induced bone loss ( Invernizzi et al, 2020a ; de Sire et al, 2021b ; Pagnotti et al, 2021 ; Singh and Toohey, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, rehabilitation plays a key role in the management of BC survivors with growing evidence highlighting its positive effects in improving functional outcomes and psychosocial well-being of BC patients ( Reid-Arndt et al, 2009 ; Zaidi et al, 2017 ; Kudre et al, 2020 ; Sleight et al, 2022 ). Hence, rehabilitation might improve the symptoms of patients with breast cancer–related lymphedema ( Invernizzi et al, 2019 ; Michelotti et al, 2019 ; de Sire et al, 2021a ; Carretti et al, 2022 ; Muñoz-Alcaraz et al, 2022 ; Omar et al, 2022 ), cancer-related fatigue ( Wirtz and Baumann, 2018 ; Adams et al, 2019 ; Invernizzi et al, 2020b ; Marechal et al, 2020 ; Licht et al, 2021 ), axillary web syndrome ( de Sire et al, 2020 ; Ravichandran et al, 2020 ; Tay et al, 2021 ), aromatase inhibitor–induced arthralgia ( Harris et al, 2012 ; Winters-Stone et al, 2012 ; Grizzi et al, 2020 ), and cancer treatment–induced bone loss ( Invernizzi et al, 2020a ; de Sire et al, 2021b ; Pagnotti et al, 2021 ; Singh and Toohey, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, endoscopic dilation can lead to improvement in dysphagia in select patients at risk of pharyngo‐esophageal junction stricture 24 . Tailored rehabilitation exercises targeting shoulder dysfunction can improve function and HRQOL, 18 which aligns with a recent systematic review identifying the beneficial effects of physical rehabilitation in cancer survivorship 44 . And a self‐help exercises program suggested that dysphagia‐related QOL may improve modestly, even among long‐term survivors 16 .…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, a direct relationship has been established between this symptomatic improvement and an improvement in terms of dependency. Analyzing the existing literature, we can see how this correlates directly with studies by Campbell, Covington or Sleight and his collaborators [43][44][45].…”
Section: Discussionmentioning
confidence: 78%